Using tDCS as an Add-On Treatment Prior to FES Therapy in Improving Upper Limb Function in Severe Chronic Stroke Patients: A Randomized Controlled Study - Shaheiwola, Nuerjiayi; Zhang, Bin; Jia, Jie; Zhang, Dingguo (Frontiers in Human Neuroscience, 2018)
Background: Upper limb function recovery is of vital importance for stroke patients. However, it is difficult to get ideal recovery, especially for patients with severe chronic stroke. As the first randomized controlled long-term trial combining bilateral transcranial direct current stimulation (tDCS) and functional electrical stimulation (FES) therapy, this study examined the efficacy of a novel protocol that included applying tDCS as an add-on treatment prior to FES therapy over the course of a 4-week program. Methods: Thirty subjects with severe chronic stroke were randomized to either Group A (active tDCS+FES)(N=15) or Group B (sham tDCS+FES)(N=15). Five assessments including 3 behavioral outcome measurement scales [the Fugl-Meyer scale (cFMA), the Wolf motor function test (WMFT) and the modified Ashworth scale (MAS)], the surface electromyography (sEMG) evaluation and the transcranial magnetic stimulation (TMS) assessment were performed to evaluate subjects before and after the overall therapy. Results: In Group A, the combined protocol was well tolerated by all patients and induced significant improvements in upper extremity motor abilities in terms of the assessments of cFMA [t(14)=-5.658, p<0.05], WMFT [t(14)=-3.746, p<0.05], MAS [t(14)=5.236, p<0.05], sEMG and TMS. The results of between-group comparisons showed there was a significant difference between Group A and Group B in terms of the assessments of cFMA [t(28)=2.223, p<0.05], WMFT [t(28)=-2.152, p<0.05] and sEMG [F(1, 196)=0.918, p<0.05]. Conclusion: The proposed protocol can facilitate improvements in upper extremity motor abilities in severe chronic stroke patients and is more beneficial than the protocol with FES therapy alone. Our results showed efficacy of the new paradigm with combined intervention in both the central nervous system and the peripheral nervous system.